Commercialization of Medicinal Plants in Java Island, Indonesia - Nugroho, Ignatius Adi; Nurrochmat, Dodik Ridho; Hardjanto, Hardjanto (Jurnal Manajemen Hutan Tropika, 2016)
The benefit and transaction cost flow which people earn economically and socially from wild medicinal plant harvesting are addressed in this study. The objectives of this study are three aspects: defining how many users are involved in utilization of medicinal plant raw materials (MPRM), how users describing their perception and motivation and describing benefit and transaction cost which influence users to harvest the plants. Results showed that utilization of medicinal plants in Java is still widely used as commercial products then medical services. There are 41 stakeholders who involved in this study and the highest motivation and perception in production and industrial clusters are economic interest. But stakeholder’s perception and motivation in traditional healthcare cluster is social interest. The different motivation and perception in both clusters causing stakeholder who are work in traditional healthcare lack of market information, but they are important if the government will improve the traditional medicine. Recommendation of this study is that medicinal plants need further research and product development which can help to expand the medicinal plant culture area in the natural forest. By this reason, government should develop good political will to increase the medicinal plant resources for public healthcare.